Designing a stress and anxiety support tool to help young adults with autism in daily living - Espinosa, Marcela A.; Escobedo Bravo, Lizbeth Olivia (My University, 2023)
Individuals with autism may experience higher stress and anxiety levels for longer periods than their neurotypical peers. Traditional techniques to provide stress relief and anxiety management include support, which reminds people of how to face stressful situations. Some technological proposals supporting the user include strategies for detecting and monitoring stress levels. In this research, we conducted an iterative user-centered study aiming to understand how young adults with autism deal with stress in real-life situations. We proposed a set of five design principles that will serve as guidelines to develop assistive anxiety management technology for individuals with autism. We then developed a set of low-fi prototypes and selected SATORI, a support tool composed of three interfaces, to help young adults with autism autonomously manage the anxiety caused by stressful situations in their daily life. We evaluated our proposed design principles using SATORI with eight young adults with autism. The results show a positive perception of the design principles on what SATORI is based on, as participants perceived that SATORI could help them in their daily life to manage stress and channel anxiety.
Interacting with Computers
Keywords: Autism; Young adults; Campus Tijuana